Enhancing Clinical Competence of New Graduate Nurses to Improve The Quality of Patient Care - Matlhaba, Kholofelo Lorraine (Journal of Ners and Midwifery, 2025)
Nurses are expected to be competent with the ability to perform independently and deliver safe patient care. This paper aimed to report the measures to enhance the clinical competence of new graduate nurses with the intention of improving quality of patient care in public hospitals. This research was a qualitative design with focus group discussions and individual interviews used to collect data from seven public hospitals in three districts of Northwest Province, South Africa, during the period, of September, and November 2021. Thematic data analysis was employed to analyze the collected data. The result of this research was two themes with eight sub-themes reported as follows: 1) Dealing with theory and education gaps, and 2) Identify and eliminate organizational and institutional barriers. The conclusion was a theory-practice gap can lead to a lack of confidence and incompetence which will in return hinder safe practice and quality performance. On the other hand, organizational and institutional challenges can compromise support for newly graduated nurses during their transition period. Therefore, attending to the measures to enhance new graduate nurses’ clinical competence will benefit the healthcare facilities, as it would have positive effects on patient care. It is therefore suggested that future studies may use different study methods including the different populations such as the new graduate nurses themselves, and operational managers from the other healthcare facilities such as clinics and primary healthcare centers.